Modified perturb & observe maximum power point technique for solar photovoltaic systems - Premkumar M.; Sudhakar Babu T.; Sowmya R. (International Journal of Scientific and Technology Research, 2023)
This paper discusses the Modified Perturb & Observe (MP&O) maximum power point tracking (MPPT) algorithm for solar photovoltaic (PV) power generation system. The most crucial aim of this paper is to overcome the demerits of the very old P&O algorithm such as the inability to track the maximum power point (MPP), steady-state oscillations, and deviation in tracking direction in the course of partial shading conditions (PSCs), and extreme shading conditions (ESCs). By varying the step size of the perturbation in the traditional P&O algorithm, it can able to detect the maximum power point (MPP) in any situation, and it can be implemented with less cost while compared to the conventional models. The proposed method is verified using MATLAB/Simulink simulations by applying all test conditions. The simulation result shows that the proposed method can able to track the maximum power point successfully under all the circumstances. 2020 IJSTR.